Kurgan Tunnug 1—New Data on the Earliest Horizon of Scythian Material Culture. (16th November 2020) - Sadykov, Timur; Caspari, Gino; Blochin, Jegor
ABSTRACT: Questions surrounding the emergence of highly mobile nomadic pastoralism and the origins of the associated Scythian material culture have a long history in Eurasian steppe archaeology, but advances in knowledge have been hindered by a lack of data. Here we present new findings on the Early Iron Age royal burial mound Tunnug 1 in Tuva. While the site belongs to the same cultural tradition as Arzhan 1, the conceptual roots of the funerary ritual architecture can be traced to precursors in the Mongun Taiga culture and the Mongolian deer stone khirigsuur complex. The clay architecture uncovered at Tunnug 1 does not find any regional comparisons and possibly hints towards a western Central Asian contribution to the formation of the earliest Scythian horizon. Our research demonstrates the value of a multi-disciplinary approach to documenting monumental earthen architecture, including technical approaches (satellite imagery, aerial photographs, 3D models, digital elevation models, geophysics, and radiocarbon dating) with an analysis of construction material and associated finds.